Kombinasi Massage Otot Pectoralis Mayor dan Massage Endorphine pada Ibu Hamil Trimester III terhadap Produksi ASI Ibu Post Partum Di Kota Palu - Uddin, Rafika; Kusika, Sri Yanti (Window of Health : Jurnal Kesehatan, 2019)
The inhibiting factor in breastfeeding is the production of breastfeeding it self. The production of breast milk which is less and slowly exits can cause the mother not to give enough milk to her baby. Stimulating breastmilk production can be done by trying to stimulate prolactin and oxytocin hormones including by carrying out breast care on the skin, through pectoralis major muscle massage and endorphine massage to accelerate oxygen and make the mother feel relaxed. The aim of the study was to determine the effect of the combination of pectoralis major muscle massage and endorphine massage in third trimester pregnant women on breast milk release in post partum mothers. This type of research is quasi-experimental with the design of the Static-Group Comparasion. The study was conducted in September-November 2018 in the area of the Kamonji Health Center in the City of Palu. The population consisted of an intervention group of 24 people combined treatment of pectoralis major muscle massage followed by endorphine massage, and a control group of 24 people not given treatment. Sampling using the executive sampling technique. Univariate analysis and bivariate analysis. The results of this study obtained by the intervention group had an average volume of breast milk of 1.36 cc, a minimum value of 05, cc and a maximum of 2.3 cc. while the control group has an average value of 0.38 cc, a minimum value of 0.1 cc and a maximum of 0.8 cc. it means there is a difference in the average volume of breast milk in the intervention group higher than the control group. This result is based on thestatistic Mann-Whitney Test obtained p value = 0,000. It was concluded, the combination of major pectoralis muscle massage and endorphine massage in third trimester pregnant women was effective against post partum breast milk release. Suggestion, the need for health center officers to apply this complementary therapy so that the target of exclusive breastfeeding is achieved.